Strategies and methods of HIV prevention among Malaysian women: a literature review - Abd Manaf, Rosliza; Ibrahim, Faisal (Community Health Society Malaysia, 2015)
Background: The scale and intensity of HIV epidemic among women worldwide and in Malaysia is increasing at an alarming rate. Their difference in vulnerability, coupled with the heightened risk of heterosexual transmission demands specific preventive strategies for controlling HIV epidemic among women. This article reviews the strategies and methods of HIV prevention which may be used for women, specifically within the Malaysian context.